2013
DOI: 10.5152/dir.2013.149
|View full text |Cite
|
Sign up to set email alerts
|

CT-based weight assessment of lung lobes: comparison with ex vivo measurements

Abstract: ORIGINAL ARTICLE PURPOSE We aimed to evaluate the validity of lung lobe weight assessment via computed tomography (CT) by comparing CT-derived and ex vivo measurements. MATERIALS AND METHODSUnenhanced CT scanning was performed in 30 consecutive patients before lobectomy for lung cancer. The CT images were analyzed using research software after allowing for lobar weight quantitation. The lobar weight estimated by CT was then compared with that measured after surgery using a precision scale (ex vivo measurement)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Other authors have shown that CT properly quantifies the weight of inanimate objects [ 8 ], artificial lung models [ 13 ], exsanguinated [ 14 ] and frozen [ 15 ] lungs and surgically excised pulmonary lobes [ 16 ]. Results acquired in vivo can be less accurate.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have shown that CT properly quantifies the weight of inanimate objects [ 8 ], artificial lung models [ 13 ], exsanguinated [ 14 ] and frozen [ 15 ] lungs and surgically excised pulmonary lobes [ 16 ]. Results acquired in vivo can be less accurate.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis was performed on total volume to avoid partial volume artifact. Calculation of weight of differently aerated areas was made through volumes and mean density (lung weight = lung volume × (mean density + 1000)/1000) [45][46][47].…”
Section: Postprocessing Analysismentioning
confidence: 99%
“…with different gas/tissue ratios, which can turn critically in the clinical work-up of a symptomatic COVID-19 patient [39,[45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a noise may be attenuated by evaluating the lung weight, which takes into account both lung volume and lung density. 151 QCT was reported to enable objective tracking of the changes in lung weight and air-space inflation produced by a standard intervention, as in pulmonary alveolar proteinosis, suggesting lung weight could be a reliable metric to assess longitudinal change in ILDs (e.g. diffuse acute lung disorders).…”
Section: State Of the Artmentioning
confidence: 99%